Outcome of Injection Botulinum Toxin in Blepharospasm - Amatya, Malita; Limbu, Ben; Sthapit, Purnima Rajkarnikar; Gurung, Hom Bahadur; Saiju, Rohit (Nepalese Journal of Ophthalmology, 2021)
Introduction: Blepharospasm is a condition of involuntary spasm of the orbicularis oculi muscle which leads to intermittent or complete closure of the eyelids. Botulinum toxin is the currently recommended first line treatment for such blepharospasm. This study aims to find out the outcome of injection Botulinum toxin Type A in Blepharospasm. Materials and methods: It was a hospital based, prospective, interventional study conducted on patients diagnosed as Benign essential blepharospasm (BEB), Meige syndrome (MS) and Hemifacial spasm (HFS) by oculoplastic surgeon at Oculoplasty department OPD, Tilganga Institute of Ophthalmology, from December 2018 to November 2019. After taking all standard precautions for botulinum toxin injections, 6 to 8 sites for injecting 2.5 to 5 IU of the toxin were given. All the patients were evaluated before and after injections according to Jankovic spasm grading and improvement in functional impairment scale and followed on one week, one month, three month and when the symptoms reappeared. Results: A total of 43 cases which included 32 cases of Benign essential Blepharospasm, 9 Hemifacial spasm and 2 Meige syndrome. The mean Jankovic severity score was 3.51 ± 0.51 (range 3-4). The mean improvement in functional score was 2.60 ± 0.54 (range 1-3), was statistically significant (p-value <0.001).The effective period of injection was 130 ± 20.82 (93 – 189) days.38 patients had repeated injections after reappearance of symptoms. 4 patients had side effects of redness and hematoma at one site. Conclusion: This study concludes that Botulinum toxin type A is effective in the management of Benign essential blepharospasm, Hemifacial spasm and Meige syndrome. This along with a good safety profile justifies its role as a first line treatment therapy in blepharospasm. However, it is a temporary treatment option where the effect lasts for a short period of time and repeated injections are required.